Hereditary thrombocytopenia, perioperative management in cardiac surgery patients - Antonela Estefania Moran Palomeque; Dra.Karola Adriana Puente Mosquera; Dr. Julio Cesar Ojeda Sánchez; Dra. Maria Daniela Encalada Torres; Juan Bernardo Flores Sigüenza (International Journal of Medical Toxicology and Legal Medicine, 2024)
Hereditary thrombocytopenia (HT) poses a significant challenge in the perioperative management of patients undergoing cardiac surgery due to the increased risk of bleeding complications. The aim of this study was to analyze current perioperative management strategies for HT in cardiac surgery patients. An exhaustive literature review in several databases was used, selecting 43 high quality studies. The results emphasize the importance of a thorough preoperative evaluation, including detailed clinical history, physical examination, specific platelet function tests and strict follow-up by hematology. It is therefore important to emphasize that optimal perioperative management requires a multidisciplinary approach, with individualized strategies for each patient. Key measures include optimizing platelet counts through transfusion support, the use of hemostatic agents and drugs that improve platelet function, and the use of meticulous surgical techniques. In addition, close monitoring of hemostasis is essential throughout the procedure and in the immediate postoperative period. In conclusion, perioperative management of HT in cardiac surgery requires a comprehensive approach, coordinated according to individual needs. Only through methodical planning, multidisciplinary teamwork and continuous monitoring can the results be optimized and the risks associated with this complex hematological condition be minimized.